Dosimetric and Clinical Predictors for Acute and Late Gastrointestinal Toxicity Following Chemoradiotherapy of Locally Advanced Anal Cancer. Issue 1 (January 2022) - Nilsson, M.P.; Gunnlaugsson, A.; Johnsson, A.; Scherman, J.
Abstract: Aims: To analyse dosimetric and clinical predictors for acute and late gastrointestinal toxicity following chemoradiotherapy of anal cancer. Materials and methods: Consecutive patients with locally advanced (T2 ≥4 cm – T4 or N+) anal cancer were selected from an institutional database ( n = 114). All received intensity-modulated radiotherapy with concomitant 5-fluorouracil and mitomycin C. Gastrointestinal toxicity was retrospectively graded according to Common Terminology Criteria for Adverse Events (CTCAE) version 5.0 and bowel cavity, small bowel and large bowel were contoured. Dosimetric and clinical variables were tested for associations with acute grade ≥3 gastrointestinal toxicity and late grade ≥2 gastrointestinal toxicity using the Mann–Whitney test, area under receiver operating characteristic curve (AUC) and logistic regression. Results: The median follow-up was 40 months. Acute grade ≥3 gastrointestinal toxicity was seen in 51 (44.7%) of the patients; late grade ≥2 gastrointestinal toxicity was seen in 36 of the patients (39.6% of 91 patients with >1 year recurrence-free follow-up). Bowel cavity V30Gy was the best dosimetric predictor for acute gastrointestinal toxicity (AUC 0.633; P = 0.02). Large bowel V20Gy was the best dosimetric predictor for late gastrointestinal toxicity (AUC 0.698; P = 0.001) but showed no association with acute gastrointestinal toxicity. In multivariate logistic regression, increasing age was significantly associated with acute gastrointestinal toxicity; smoking and large bowel V20Gy were significantly associated with late gastrointestinal toxicity. Patients who experienced acute grade ≥3 gastrointestinal toxicity were not at an increased risk of late grade ≥2 gastrointestinal toxicity (odds ratio 1.3; P = 0.55). Conclusions: Factors of importance for acute and late gastrointestinal toxicity were not the same. Bowel cavity V30Gy is a good metric to use for the prediction of acute gastrointestinal toxicity, but the results of our study indicate that individual large and small bowel loops need to be contoured for better prediction of late gastrointestinal toxicity. The role of the large bowel as an important organ at risk for late gastrointestinal toxicity merits further research. Highlights: Early and late gastrointestinal toxicity was common following chemoradiotherapy of anal cancer Predictors for early and late gastrointestinal toxicity were not the same Dose to large bowel (V20Gy) was the most important predictor for late gastrointestinal toxicity Individual large bowel loops need to be contoured to predict late gastrointestinal toxicity